2014
DOI: 10.1111/nph.13189
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of metabolic gene clusters in Arabidopsis thaliana

Abstract: Recent discoveries have revealed that the genes for the biosynthesis of a variety of plant specialized metabolites are organized in operon-like clusters within plant genomes. Here we identify a regulatory process that is required for normal expression of metabolic gene clusters in Arabidopsis thaliana. Comparative gene expression analysis of a representative clustered gene was performed in a set of chromatin mutant lines. Subsequently, metabolite levels were analysed by GC-MS and the local chromatin structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…Expression was consistently down-regulated in the hta9/hta11 double mutant, which is mutated in two of the three H2A.Z genes (44), which was also found to be associated with metabolic cluster activation (11,12), but not in any other mutant. Thus, we next investigated the hta9/hta11 mutant in more depth: we assayed the expression of all GOIs as well as the flanking genes of these clusters (Supplemental Figure S12B).…”
Section: Resultsmentioning
confidence: 99%
“…Expression was consistently down-regulated in the hta9/hta11 double mutant, which is mutated in two of the three H2A.Z genes (44), which was also found to be associated with metabolic cluster activation (11,12), but not in any other mutant. Thus, we next investigated the hta9/hta11 mutant in more depth: we assayed the expression of all GOIs as well as the flanking genes of these clusters (Supplemental Figure S12B).…”
Section: Resultsmentioning
confidence: 99%
“…This inhibitory mechanism is mediated by the deposition of H2A.Z at a set of anthocyanin biosynthesis genes, including TT3 , TT4 , TT5 , TT6 and TT7 . H2A.Z can regulate the expression of gene clusters (Wong & Wolfe, ; Nutzmann & Osbourn, ), as well as a whole gene family whose members are highly conserved but distributed throughout the genome (Cai et al ., ). Here, we showed that H2A.Z‐containing nucleosomes can also mediate the chromatin‐level regulation of multiple genes in a key plant metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in Arabidopsis has revealed gene cluster‐specific signatures of chromatin modification that are associated with localized, coordinated regulation of the component genes. Specifically, metabolic clusters have been found to be enriched for histone 3 lysine trimethylation (H3K27me3) and histone 2 variant H2A.Z, which are associated with cluster repression and activation, respectively (Nützmann & Osbourn, ; Yu et al ., ). These same chromatin modification signatures also were detected in metabolic gene clusters of maize and oat, suggesting that chromatin‐mediated co‐regulation may be a general phenomenon for at least some classes of metabolic cluster.…”
Section: Discussionmentioning
confidence: 99%